A Qualitative Analysis and Systematic Literature Review in Enhancing Leadership Competencies for Sustainable Maritime Practices in Vocational Training - Tri Cahyadi; Winarno Winarno; Riyanto Riyanto; Larsen Barasa; Titis Ari Wibowo; Cris Kuntadi; Irene Evi Krismawati; Marudut Bernadtua Simanjuntak (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The maritime industry is facing a critical shift toward sustainability, particularly through the green shipping transition. This research was conducted to explore how maritime vocational programs are developing leadership competencies necessary to manage sustainable maritime practices. Previous studies have largely focused on technical skills, with limited attention to leadership development in the context of sustainability. This research aims to fill this gap by addressing the preparedness of maritime education in cultivating leaders who can drive the green transition. The study sought to answer key questions about how leadership competencies are integrated into vocational training and the extent to which sustainability is incorporated into maritime curricula. The analysis utilized a combination of a Systematic Literature Review (SLR) and qualitative interviews with 10 maritime professionals, lecturers, and graduates. The SLR identified key competencies and frameworks in sustainable leadership, while the interviews provided insights into the current state of maritime education. The results indicate that while sustainability is increasingly recognized, there are gaps in leadership training, practical exposure to green technologies, and industry collaboration. The findings suggest that maritime vocational programs must adopt a more integrated approach to leadership development and sustainability. By embedding sustainability across curricula and providing hands-on learning opportunities, educational institutions can better prepare future maritime leaders. This research contributes to improving maritime education by addressing the intersection of leadership and sustainability.